(untitled) (Archive of Conferences, 2022)
The materials show the use of solar heat supply systems in the conditions of the city of Karshi, mainly in hot water supply systems. These systems can be used all year round, but subject to the availability of an additional source of energy in case of peak load or insufficiency of solar energy